E-commerce law for business managers - Chatterjee, C. (Charles); Chartered Institute of Bankers (Canterbury : Financial World, 2002)
This is a guide to the legal issues of launching a commercial internet site, aimed specifically at the smaller business. Issues addressed include e-commerce security, corporate identity and service provision. The book is designed as a legal reference for anybody who conducts business electronically. The book's clear and practical layout should enable commercial, marketing or IT managers to dip in and understand key legislation for themselves. The scope of the book extends beyond matters relating to online financial transactions. Chapters cover issues such as concluding contracts over the internet, intellectual property rights, domain names and email marketing.
"Financial World Publishing publications are published by The Chartered Institute of Bankers" - t.p. verso.
&#x000A
Includes bibliographical references and index.
oif 27/02/15
Loan
Keywords: Electronic commerce -- Law and legislation -- England; Electronic commerce -- Law and legislation -- Wales; Electronic commerce -- Law and legislation -- European Union countries